Studies on 3-Diethyl-aminocarbonyl-1,4;5,6,7,8-hexahydroquinoline Derivatives and their Calcium Channel Antagonistic Activities in vitro - Kısmetli, Emrah; Şafak, Cihat; Erol, Kevser; Sırmagül, Başar; Linden, Anthony (Arzneimittelforschung, 2004)
In this study, thirteen 2,6,6-trimethyl-3-carbamoyl-4-aryl-5-oxo-1,4,5,6,7,8-hexahydroquinoline derivatives were synthesized and screened for their calcium channel antagonistic actitivities. The hexahydroquinoline derivatives were synthesized according to Hantzsch reaction. The structures of the compounds were elucidated by IR, 1H-NMR, 13C-NMR, Distortionless Enhancement Polarization Transfer (DEPT), Correlation Spectroscopy (COSY), mass spectroscopy and elemental analyses.The calcium antagonistic activities of the compounds were determined by tests performed on isolated rat ileum and lamb carotid artery. In isolated rat ileum, compounds 8, 12 and 13 were found to be more active than nicardipine (CAS 55985-32-5) at a concentration of 10−5 mol/L. At the concentration 10−4 mol/L, compounds 7 and 12 were more active than nicardipine and compounds 5, 8 and 13 were equipotent. In lamb carotid artery studies, at the concentration 10−5 mol/L all compounds were found to be less active than nicardipine; at the concentration 10−4 mol/L compounds 5 and 13 showed greater inhibition than nicardipine. At this concentration, compound 9 was found to be as active as nicardipine.
Keywords: Calcium antagonists; CAS 55985-32-5; Hexahydroquinolines, calcium antagonist activity, in vitro studies, synthesis; Nicardipine